ANALYSIS OF THE “DIGITAL PRANK” PHENOMENON FROM THE PSYCHOLOGY PERSPECTIVE - Akhmad Liana Amrul Haq; Moch. Imron Rosyidi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
This study aims at understanding the motivations and emotions of prank proprietors. The prank phenomenon that is now gaining popularity in society is seen as something that causes material losses such as money and goods as well as immaterial such as trauma and distrust. The informan of this study are 3 (three) YouTubers who have created prank content and uploaded it to YouTube (prank proprietors). This research was conducted in DKI Jakarta and Central Java. The data were collected through a phenomenological approach by conducting interviews to focus more on the concept of a phenomenon. The results show that there are two types of pranks: the pranks that go beyond the boundaries of fairness that potentially harm others and the pranks that go on the verge of fairness that does not harm others. The actors produce pranks to make entertaining content, hone creativity, and get financial profits.